The Role of Digital Marketing, Influencer Marketing and Electronic Word of Mouth (eWOM), on Online Purchase Decisions for Consumers of Private University Students in Bandung West Java - Dadang Munandar (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study is to analyze the relationship of digital marketing to online purchasing decisions, Influencer Marketing to online purchasing decisions, electronic word of mouth (eWOM) to online purchasing decisions on consumers of private university students in Bandung. A quantitative approach is used in this study. This study used an online questionnaire as a primary data collection tool. Data were analyzed using descriptive statistical analysis, and PLS-PM (Partial Least Square-Path Modeling) with SmartPLS 3.0 software. The analysis was carried out on two submodels, namely the measurement model or the outer model and the structural model (structural model) or the inner model. The outer model shows how the manifest variable represents the latent variable it measures, while the inner model shows the power of estimation between latent variables. Goodness of fit structural model in PLS analysis is in the form of predictive-relevance value (Q2), which is calculated based on the coefficient of determination (R2) of each endogenous variable. Objects that will be used as respondents in this study are consumers who use e-commerce, namely consumers of private university students in Bandung. The variables observed in this study were digital marketing, influencer marketing and e-WOM. The number of samples was 190 consumer respondents from private universities in Bandung, the sampling technique used was purposive sampling. The respondent's criteria is that they have transacted using e-commerce. Collecting data by distributing questionnaires conducted online through social media to respondents. The results of this study are digital marketing has a positive effect on online purchasing decisions, Influencer marketing has a positive effect on online purchasing decisions, Electronic Word of Mouth (eWOM) has a positive effect on online purchasing decisions.Â